Cyberbullying Across the Globe Gender, Family, and Mental Health - Navarro, Raúl; Yubero, Santiago; Larrañaga, Elisa (Springer International Publishing : Imprint: Springer, 2016)
This book provides a much-needed analysis of the current research in the global epidemic of electronic bullying. Scholars and professionals from the Americas, Europe, and Asia offer data, insights, and solutions, acknowledging both the social psychology and technological contexts underlying cyberbullying phenomena. Contributors address questions that are just beginning to emerge as well as longstanding issues concerning family and gender dynamics, and provide evidence-based prevention and intervention strategies for school and home. The global nature of the book reflects not only the scope and severity of cyberbullying, but also the tenacity of efforts to control and eradicate the problem. Included in the coverage:  • Gender issues and cyberbullying in children and adolescents: from gender differences to gender identity measures.  • Family relationships and cyberbullying. • Examining the incremental impact of cyberbullying on outcomes over and above traditional bullying in North America. • A review of cyberbullying and education issues in Latin America. • Cyberbullying prevention from child and youth literature. • Cyberbullying and restorative justice. Cyberbullying across the Globe is an essential resource for researchers, graduate students, and other professionals in child and school psychology, public health, social work and counseling, educational policy, and family advocacy.